Crude oil analysis by X‐ray scattering technique. (30th January 2019) - Oliveira, Davi F.; Silva, Ana Cecília; Figueiredo, Willians P.; Anjos, Marcelino J.; Lopes, Ricardo T.
Abstract : Composed of hydrocarbons and other substances, petroleum is classified as a nonrenewable source of energy. In its unrefined form, it is called crude oil. Currently, its derivates are widely used in domestic and industrial environments, with the greatest exponent being motor fuels and lubricating oils. Due to the overwhelming demand, new oil wells in the presalt region of Brazil are going to be drilled, which will, in its turn, increase the demand for analysis and require the use of less costly technologies. The purpose of this paper is to present an experimental method that aims at characterizing crude oil samples through their X‐ray scattering profiles without the need for any chemical preparation to be performed in advance, which will enable this method to be used for analyzing samples immediately after their extraction. For the experiment, a portable X‐ray scattering system composed by an X‐ray tube (silver anode) and a Si‐PIN detector was used in order to analyze samples from different wells. The process consisted in establishing a linear relationship between the effective atomic number and the ratio between peak intensities of Compton and Rayleigh scattering from known samples. The linear function, verified experimentally, was then applied to samples of crude oil, and the results showed that it is possible to characterize them on the basis of the Rayleigh to Compton scattering ratio. After the analysis, a multiple comparison test performed on the samples proved that this methodology indeed allows to differentiate samples of different origins and to verify the compatibility of samples extracted from the same well.